2019
DOI: 10.1093/biolre/ioz159
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cholesterol efflux: ATP-binding cassette transporters and follicular fluid HDL regulate cholesterol content in mouse oocytes†

Abstract: High density lipoproteins (HDL) take up cholesterol from peripheral tissues via ABC transporters and deliver it to the liver via scavenger receptor class B type I (SR-B1). HDL are the main lipoproteins present in follicular fluid (FF). They are thought to derive from plasma, but their origin is still controversial. SR-B1 knock-out (KO) mice have provided important evidence linking HDL metabolism and female fertility. These mice have cholesterol-rich circulating HDL and female infertility that can be restored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…The results showed that both of these lncRNAs and mRNAs were involved in the regulation of ATP binding, protein binding, cell differentiation and transcription by RNA polymerase II. For example, ATP binding has been shown to be involved in the regulation of oocyte formation (Quiroz et al, 2020). The RNA polymerase II involved in a combinatorial control of the timely regulated Spo11 splicing during the process of meiosis (Cesari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that both of these lncRNAs and mRNAs were involved in the regulation of ATP binding, protein binding, cell differentiation and transcription by RNA polymerase II. For example, ATP binding has been shown to be involved in the regulation of oocyte formation (Quiroz et al, 2020). The RNA polymerase II involved in a combinatorial control of the timely regulated Spo11 splicing during the process of meiosis (Cesari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism disorders including a high plasma cholesterol level and high nonesterified cholesterol level in the extraovarian environment account for the infertility phenotype of Scarb1 -deficient ( Scarb1 −/− ) mice. When altering the structure or quantity of abnormal HDL by silencing the ApoA1 gene or lowering cholesterol levels in blood by feeding probucol, the fertility of Scarb1 -deficient mice was partially or completely restored ( Miettinen et al, 2001 ; Quiroz et al, 2020 ). Human plasma cholesteryl ester transfer protein (CETP) transfers cholesteryl esters from HDL and LDL to VLDL, which in turn binds hepatic LDL receptor (LDLR) or VLDL receptor (VLDLR) to transport cholesterol from peripheral tissues to the liver (reverse cholesterol transport).…”
Section: Lipoprotein Transportmentioning
confidence: 99%
“…The results revealed that both of these DE mRNAs and DE lncRNAs were participated in the regulation of protein binding, ATP binding, cell differentiation, and transcription by RNA polymerase II. It can be illustrated that ATP binding has been reported to participate in the oogenesis regulation ( 34 ). The RNA polymerase II was reported to be involved in the combinatorial control of Spo11 splicing, which is timely regulated during meiosis ( 35 ).…”
Section: Discussionmentioning
confidence: 99%